2020
DOI: 10.3390/ma13133034
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering (SLS) and Post-Processing of Prosopis Chilensis/Polyethersulfone Composite (PCPC)

Abstract: The range of selective laser sintering (SLS) materials is currently limited, and the available materials are often of high cost. Moreover, the mechanical strength of wood–plastic SLS parts is low, which restricts the application of a SLS technology. A new composite material has been proposed to address these issues, while simultaneously valorizing agricultural and forestry waste. This composite presents several advantages, including reduced pollution associated with waste disposal and reduced CO2 emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…It exhibits a stable temperature performance and excellent properties. PES is widely used in the various applications of engineering plastics and composite materials (Li et al , 2020; Idriss et al , 2020b). The use of PCP not only ensured an excellent bonding between the PCP and PES powder but also increased the stability, flexibility and ease of synthesis of the PCPC.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It exhibits a stable temperature performance and excellent properties. PES is widely used in the various applications of engineering plastics and composite materials (Li et al , 2020; Idriss et al , 2020b). The use of PCP not only ensured an excellent bonding between the PCP and PES powder but also increased the stability, flexibility and ease of synthesis of the PCPC.…”
Section: Methodsmentioning
confidence: 99%
“…All the test samples in this experiment were printed using an AFS-360 SLS (AM) (Beijing Longyuan Technology, Ltd., Beijing, China). In a previous study, it was identified that the optimal mixing ratio of the PCP to PES powder to produce the PCPC was 10:90 (wt/wt), which was taken from (Li et al , 2020; Idriss et al , 2020b). The laser wavelength for SLS was 10.6 µm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations